2020
DOI: 10.1101/2020.08.25.266122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multivariate associative patterns between the gut microbiota and large-scale brain network connectivity

Abstract: Research on the gut-brain axis has accelerated substantially over the course of the last years. Many reviews have outlined the important implications of understanding the relation of the gut microbiota with human brain function and behavior. One substantial drawback in integrating gut microbiome and brain data is the lack of integrative multivariate approaches that enable capturing variance in both modalities simultaneously. To address this issue, we applied a linked independent component analysis (LICA) to mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Amongst the studies with healthy participants, relevant findings were obtained with the use of brain functional magnetic resonance imaging (fMRI). For example, it was identified that the Bifidobacterium concentration is positively correlated with the increasing connectivity of the frontal nodes of the default mode network, while the prevalence of Prevotella_9 and Bacteroides is negatively correlated 20 . It was also shown that participants who received probiotics, compared to a control group, had decreased functional connectivity between the frontal pole and frontal medial-cortex during resting-state fMRI 12 , as well as a significant reduction in brain activity in sensory and affective regions, such as the insula, and increased activity in cortical regulatory regions, such as the DLPFC and MPFC, during a standardized emotional face recognition task 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the studies with healthy participants, relevant findings were obtained with the use of brain functional magnetic resonance imaging (fMRI). For example, it was identified that the Bifidobacterium concentration is positively correlated with the increasing connectivity of the frontal nodes of the default mode network, while the prevalence of Prevotella_9 and Bacteroides is negatively correlated 20 . It was also shown that participants who received probiotics, compared to a control group, had decreased functional connectivity between the frontal pole and frontal medial-cortex during resting-state fMRI 12 , as well as a significant reduction in brain activity in sensory and affective regions, such as the insula, and increased activity in cortical regulatory regions, such as the DLPFC and MPFC, during a standardized emotional face recognition task 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies have explored the effects of GBA on healthy participants 8 . Nevertheless, the results thus far presented con rm the correlation between the variability of the complex gut environment and high-level brain activity 9,10,23,28,29 . A recent study explored the multivariate associative patterns between gut microbiota composition and large-scale brain network connectivity 29 .…”
Section: Introductionmentioning
confidence: 62%
“…Nevertheless, the results thus far presented con rm the correlation between the variability of the complex gut environment and high-level brain activity 9,10,23,28,29 . A recent study explored the multivariate associative patterns between gut microbiota composition and large-scale brain network connectivity 29 . It identi ed that the Bi dobacterium concentration is positively correlated with the increasing connectivity of the frontal nodes of the default mode network, while the prevalence of Prevotella_9 and Bacteroides is negatively correlated with connectivity 29 .…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations